2017
DOI: 10.1097/md.0000000000008390
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whole-body vibration training on lean mass

Abstract: Background:Whole-body vibration training (WBVT) confers a continuous vibration stimuli to the body. Although some reports have discussed the effects of whole-body vibration (WBV) on bone mineral density and muscle strength, study of WBV effects on lean mass have not been determined. The purpose of the present meta-analysis was to evaluate published, randomized controlled trials (RCTs) that investigated the effects of WBVT on lean mass.Methods:We identified only RCTs by searching databases, including Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Our findings suggested that VT did not provide sufficient stimulus for skeletal muscle hypertrophy in older adults with sarcopenia. These findings were in accordance with the systematic reviews performed by Chen et al [66] and Beaudart et al [43]. All of their results showed no impact of VT on muscle mass in regard to frail participants, participants residing in a nursing home or participants with limited mobility.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggested that VT did not provide sufficient stimulus for skeletal muscle hypertrophy in older adults with sarcopenia. These findings were in accordance with the systematic reviews performed by Chen et al [66] and Beaudart et al [43]. All of their results showed no impact of VT on muscle mass in regard to frail participants, participants residing in a nursing home or participants with limited mobility.…”
Section: Discussionsupporting
confidence: 91%
“…However, WBV training had no effect on body composition, as it was expected due to the results reported in previous studies (von Stengel et al, 2012). A recent metaanalysis about the effects of WBV training on lean mass demonstrated that this could lead to improvement in lean mass or muscle mass in younger adults, but not in other populations (Chen et al, 2017). Therefore, neuronal mechanisms may predominantly contribute to the observed strength gains in the NWBV group.…”
Section: Discussionsupporting
confidence: 56%
“…WBV training generates simulated mechanical vibrations, which in turn activate the neuromuscular control system, increase the level of excitement and the number of motor units recruited and coordinate synergistic and antagonistic muscles during rapid muscle contractions, thus enhancing muscle function (Delecluse et al, 2003). As muscle strength and lean mass are highly interrelated, WBV training could have a positive effect on muscle mass (Chen et al, 2017). Numerous intervention studies have been carried out to increase muscle mass (Chen et al, 2017) and muscle function (Goudarzian et al, 2017b;Ko et al, 2017) in the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to most clinical guidelines, exercise training is known to effectively reduce pain and improve back function in CLBP [7]. However, some patients cannot participate in conventional vigorous exercise training due to prior illness [8]. Whole body vibration (WBV) exercise has been used to train musculoskeletal systems at homes and rehabilitation clinics.…”
Section: Introductionmentioning
confidence: 99%